2011
DOI: 10.7589/0090-3558-47.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Efficacy of Two Rabies Vaccines in Wild-Caught, Captive Raccoons

Abstract: The immunogenicity and efficacy of two rabies vaccines in wild-caught, captive raccoons (Procyon lotor) were investigated. Raccoons were fed Ontario Slim (OS) baits containing a recombinant vaccinia virus-rabies glycoprotein (VRG) oral rabies vaccine, or they were given an intramuscular (IM) injection of IMRAB(®) 3 rabies vaccine. Blood samples collected before treatment and from weeks 1 to 16 posttreatment were assessed for the presence of rabies virus antibody (RVA). There were significantly more positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“… (11.8% survived); Szanto (40% survived); Brown et al . , (15.4% and 11.1% survived, respectively)]. In addition, a large amount of variation has been found in MHC genes in raccoons (Castillo et al .…”
Section: Introductionmentioning
confidence: 99%
“… (11.8% survived); Szanto (40% survived); Brown et al . , (15.4% and 11.1% survived, respectively)]. In addition, a large amount of variation has been found in MHC genes in raccoons (Castillo et al .…”
Section: Introductionmentioning
confidence: 99%
“…While foxes and coyotes tend to pick up the entire bait with their mouth, releasing a full dose of vaccine into the buccal cavity as they chew, raccoons hold the vaccine sachet on the ground and bite only small portions at a time, allowing the open sachet to leak. Pen trials have repeatedly shown raccoons spilling much of the liquid contents of the sachet (Brown et al, 2011).…”
mentioning
confidence: 99%
“…For the Central Park outbreak, oral rabies vaccine was ruled out because of the small but potential risk for vaccinia infections of humans ( 7 , 8 ), given the large volume of park visitors and poor raccoon seroconversion rates (9%–61%) ( 9 – 14 ). Depopulation was also eliminated because it would have overwhelmed the animal shelter system with demand for humane euthanasia and decapitations and because a national animal welfare organization and the public voiced opposition.…”
Section: The Programmentioning
confidence: 99%